Share-net: a case study of environmental education resource material development in a risk society - Taylor, Robert James (Rhodes University, Faculty of Education, Department of Education, 1997)
This narrative study reviews the development of Share-Net, an informal resource materials network, located within the developing environmental education activities of the Wildlife and Environment Society of South Africa. Historical shaping factors within the Society are discussed and changing views on conservation, environmental education and research are described. Rather than the research process being a utilitarian and outside endeavour for clarifying and monitoring, the research orientation of this study is one of grounded activity within and integrally part of processes of change. Within a developing story of resource materials and workshops, themes are traced and emergent tensions are critically reviewed. Teacher workshops from 1981 until 1995 are analysed and developing orientations are described. Within this review changes are evident from an orientation of 'us' informing 'them' to joint, collaborative endeavours within the development and use of resource materials. The study reviews and illuminates the Share-Net project around questions of project orientation and management and this is done through the narration of case studies. Principles and patterns emerging within these are examined to guide future resource development projects. Popularist notions of networking and structural functionalist notions of social change are also examined. Grand, modernist strategies designed to cause change in others are questioned and the role of small-scale nodes of resource material activity cooperating within an open network are clarified as useful alternatives. Local resourcing centres such as these have proved useful in supporting teachers in the development, use and adaptation of resource materials. The study also examines income and expenditure of the Share-Net project since 1988 to review economic sustainability. A case is made for sustaining the project conceptually and financially through the sales of products and services rather than through external donor sources. Finally the study raises questions and challenges within the project and proposes guiding frameworks for future review, in action, as the story continues.
Keywords: Environmental education; Environmental education -- South Africa; Environmental education -- Activity programs -- South Africa; Environmental education -- South Africa -- Information resources